2004
DOI: 10.1081/iph-200042357
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Cancer and Pro‐Apoptotic Effects of an Herbal Medicine andSaccharomyces CerevisiaeProduct (CKBM) on Human Hepatocellular Carcinoma HepG2 Cells In Vitro and In Vivo

Abstract: Hepatocellular carcinoma is a major health problem worldwide. Different treatment strategies have been developed to cope with this problem. Herbal medicine is now widely studied in both Eastern and Western countries. In this study, we used both in vitro and in vivo model to illustrate the anti-tumor effect of a product, CKBM, consisting of herbal medicine and specially processed Saccharomyces cerevisiae. Dose-dependent anti-proliferation effect was observed on in vitro growth of human hepatoma HepG2 cells afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…BLCa is a heterogeneous disease with a propensity to become invasive; thus it is essential that any treatment regime targets Table 1 and verified in Table 2. effector molecules, functional systems or metabolic pathways that are active in disease progression. MINA-05 contains a combination of botanical extracts that have been shown individually to induce cell cycle arrest, inhibit tumour growth, have antiviral activity or boost the immune responses in patients with various gastrological and urological conditions [7][8][9][10][11]23]. Additionally, MINA-05 has been shown to inhibit cellular proliferation of human androgen-sensitive and hormone refractory prostate cancer cell lines [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BLCa is a heterogeneous disease with a propensity to become invasive; thus it is essential that any treatment regime targets Table 1 and verified in Table 2. effector molecules, functional systems or metabolic pathways that are active in disease progression. MINA-05 contains a combination of botanical extracts that have been shown individually to induce cell cycle arrest, inhibit tumour growth, have antiviral activity or boost the immune responses in patients with various gastrological and urological conditions [7][8][9][10][11]23]. Additionally, MINA-05 has been shown to inhibit cellular proliferation of human androgen-sensitive and hormone refractory prostate cancer cell lines [13].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, scientific endeavors have been directed to determining the physiological and cellular mechanisms of TCM. For example, TCM and botanical extracts have been shown to reduce the growth of hepatocellular and gastric carcinomas in both in vitro and in vivo models [7][8][9][10][11]. Plant extracts have been shown to have a broad range of biological activities: extracts from Schisandra chinesis (containing lignans) have anti-apoptotic effects against lung carcinoma cells; extracts from Glycine max (rich in isoflavones), are beneficial in preventing and treating cancers and other chronic diseases and have been reported to increase IL-6 in postmenopausal women [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…The present study strongly indicated that CKBM exerted cytotoxic effect on various primary cancer cells, especially on breast and bladder cells (Table 2). Previous study also indicated CKBM's inhibition effect is cancer-specific, with no significant effect on normal liver HS68 and WRL68 cell lines [5]. Nevertheless, the mechanism by which CKBM inhibits tumor cell growth is not fully understood at present.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that CKBM possesses anti-tumor effect both in vitro and in vivo as well as the ability to induce cancer cell cycle arrest at G2/M stage [4,5], but it had no significant inhibition on normal cell growth [5]. Oral CKBM treatment inhibits gastric and liver tumor xenograft growth in nude mice [4,5]. In addition, it modulates immune functions by inducing peripheral blood mononuclear cells (PBMC) to secrete tumor necrosis factor-alpha, interleukin-6 and interleukin-8 [6].…”
Section: Introductionmentioning
confidence: 99%
“…These cells were primarily derived from liver tissues of a 15-years-old male Caucasian patient, suffering from HCC. HCC is amongst the most frequent primary types of neoplastic malignancies, involving liver (4,5). Almost all of the therapy protocols applied for treatment of HCC are associated with cytotoxicity effects.…”
Section: Introductionmentioning
confidence: 99%